Talent Management in Managerial Succession Planning: A Qualitative Study - Andi Shodiq Widodo; Ika Nurul Qamari; Siti Dyah Handayani; Mastura Roni (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
Investment in Human Resources is managed through a strategy for preparing sustainable future leaders. Talent management with the right processes of identification, recruitment and selection, development, and retention will put the right people in the right place. This study aims to determine the implementation of talent management in managerial succession planning at Soerojo Hospital. This study is qualitative research with a single case design using an in-depth interview and was conducted in October-November 2022. Informants were recruited using a purposive sampling technique, consisting of 1 key informant, 1 main informant, and 1 additional informant. The results revealed that talent management in managerial succession planning had not been fully implemented, as indicated by the subjectivity of the leaders in identifying talents, recruitment carried out after there was a vacancy, no talent pool at the selection stage, inadequate curriculum-based talent development and suboptimal talent retention because there is no guideline for implementing talent management. Therefore, Soerojo Hospital needs to establish regulations, compile curriculum and talent development methods, and create a harmonious work atmosphere for the sustainability of the organization.